1003 QIP: Improving Provision of Driving Advice Post Abdominal Surgery. (19th August 2022) - Ahmed, F; Dalip, A; Agrawal, A
Abstract: Aim: The aim of this QIP was to improve provision of driving advice post abdominal surgery. The royal college of surgeons recommends that before resuming driving after surgery, patients should be free from the sedative effects of any painkillers they may be taking, and they should be comfortable in the driving position and be able to safely control their car, including freely performing an emergency stop. Method: Relevant discharge summaries from the general surgical department at the QEQM hospital in Margate were screened from 15/01/2021 to 14/04/2021 (N=61) to assess how well the department provided driving advice. Documentation was found to be 52%. An email was sent to junior doctors outlining aims of the QIP. A second intervention was required following initial minor improvement, with a poster made and emailed to doctors rotating into the general surgical department. Results: In the first month post intervention, 15/05/21–14/05/21, a minor improvement was seen, with the documentation rate being 57% (N=56). Subsequent poster intervention to new rotating junior doctors markedly improved documentation, with monthly results from 20/08/21–19/12/21 showing documentation rates of 62% (N=86), 73% (N=103), 76% (N=111) and 86% (N=82). Conclusion: This QIP shows a marked improvement in documentation rates of driving advice post abdominal surgery. Interestingly, it also shows how timing of quality improvement advice can impact departmental outcomes. Newly joining junior doctors presented with the same intervention advice in poster format as leaving doctors were aware from their first day on their surgical rotations of best practice with regards to documenting driving advice.